A track record on SHOX: from basic research to complex models and therapy - Marchini, Antonio; Ogata, Tsutomu; Rappold, Gudrun (Endocrine reviews, 2016)
Abstract. SHOX deficiency is the most frequent genetic growth disorder associated with isolated and syndromic forms of short stature. Caused by mutations in th